2002
DOI: 10.1103/physrevlett.89.115504
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Decay of Excited Atomic States near a Carbon Nanotube

Abstract: The spontaneous decay process of an excited atom placed inside or outside a carbon nanotube is analyzed. Calculations have been performed for various achiral nanotubes. The effect of the nanotube surface is shown to increase the atomic spontaneous decay rate by up to 6 orders of magnitude compared with that of the same atom in vacuum. This increase is associated with nonradiative decay via surface excitations in the nanotube.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
61
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 14 publications
1
61
0
Order By: Relevance
“…Note that Volterra equations as above have already been used (i) for describing a single discrete energy level coupled to a featureless continuum of states [29] as well as (ii) for the case of a TLS coupled to dispersing dielectrics [9,30]. In the former case (i) a very intuitive graphical analysis was presented including, however, a spurious integral extension towards negative frequencies.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Note that Volterra equations as above have already been used (i) for describing a single discrete energy level coupled to a featureless continuum of states [29] as well as (ii) for the case of a TLS coupled to dispersing dielectrics [9,30]. In the former case (i) a very intuitive graphical analysis was presented including, however, a spurious integral extension towards negative frequencies.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Earlier theoretical studies of CNTs showed the existence of low-frequency plasmon branches [16,17] and the formation in CNTs of strongly slowed-down electromagnetic surface waves [18]. Such waves define pronounced Purcell effect in CNTs [19] and potentiality of CNTs as Cherenkov-type emitters [20]. Geometrical resonances -standing surface waves excited due to the strong reflection from the tips of finite-length CNTs -qualitatively distinguish CNTs from the planar structures investigated in [14,15].…”
mentioning
confidence: 99%
“…Recently that problem attracted new interest [31]- [36]. In [37,38] the spontaneous emission near carbon nanotubes was considered.…”
Section: Introductionmentioning
confidence: 99%